2016
DOI: 10.1111/ldrp.12102
|View full text |Cite
|
Sign up to set email alerts
|

The University Experiences of Students with Learning Disabilities

Abstract: To explore the university experiences of students with learning disabilities (LD), 63,802 responses to the 2014 Student Experience in the Research University Survey were analyzed. Compared to other students, those with self-reported LD (5.96%) had difficulty with assignments and had more obstacles caused by non-academic responsibilities and imposed by their skill levels. Students with self-reported LD sensed more bias towards people with disabilities on campus, and they were less satisfied with their overall e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 41 publications
2
74
0
7
Order By: Relevance
“…There is a small amount of data related to students’ well-being and hope: for example, there is some evidence that students with LD might self-report better well-being and a more hopeful outlook, connected to AT use. This latter result might be culture-specific to Israel, as we have seen conflicting data from the United States in less controlled studies and a large-scale quantitative survey from our laboratory (McGregor et al, 2016). …”
Section: Resultsmentioning
confidence: 86%
“…There is a small amount of data related to students’ well-being and hope: for example, there is some evidence that students with LD might self-report better well-being and a more hopeful outlook, connected to AT use. This latter result might be culture-specific to Israel, as we have seen conflicting data from the United States in less controlled studies and a large-scale quantitative survey from our laboratory (McGregor et al, 2016). …”
Section: Resultsmentioning
confidence: 86%
“…Forty-one participants with DLD and 39 with ND also participated in McGregor et al (2016). Their ages ranged from 18 to 24 years, and all were students in postsecondary institutions in the Midwest of the United States.…”
Section: Participantsmentioning
confidence: 99%
“…For example, among two-year college students, a random sample of three Canadian colleges showed that 4% of the entire student body self-reported LD (Fichten et al, 2014a). There are actually many more students on campus with LD if one takes into account those who have chosen not to disclose their disability (McGregor, et al;Wagner et al, 2005). There is a very substantial literature on students with LD, with several journals specifically devoted to this topic.…”
Section: Students With Specific Learning Disorder (Ld)mentioning
confidence: 99%
“…There are increasing numbers of North American students with LD attending two and four-year colleges after graduating from high school (McGregor, et al, 2016). For example, among two-year college students, a random sample of three Canadian colleges showed that 4% of the entire student body self-reported LD (Fichten et al, 2014a).…”
Section: Students With Specific Learning Disorder (Ld)mentioning
confidence: 99%